ANALISIS DAYA SAING UDANG INDONESIA DI PASAR EKSPOR - Ach. Firman Wahyudi; Joni Haryadi; Anisya Rosdiana (Forum Agribisnis, 2019)
Entering the international trade era, Indonesia must has the right strategy to maintain its position as an exporter in the world. One strategy which can be implemented is to increase the competitiveness of export commodities that have comparative and competitive advantages in order to be able to compete with other countries' commodities. Therefore, an in-depth study is needed on increasing the competitiveness of shrimp commodities in order to increase fisheries commodity exports. The purpose of this study was to analyze the factors which affect the competitiveness of Indonesian shrimp commodity exports in four export destination countries and to formulate strategies to increase production potential and competitiveness of shrimp commodities in the markets of the four export destinations. This research was conducted in intensive and semi-intensive pond areas in Lampung and shrimp processing centers in East Java from January until November 2016. The types of data source were primary data from observation and secondary data in panel data form. Some of the analytical methods used in analyzing competitiveness are Revealed Comparative Advantage (RCA), the gravity model for analyzing factors that influence shrimp export offerings in export destination countries. Data processing is done using Microsoft Excel 2007 and E views 6. The analysis of the competitiveness of Indonesian shrimp commodity exports showed that during the period 2004 - 2014, Indonesian shrimp commodities had a comparative advantage or strong competitiveness in Japan, the USA and the United Kingdom. Estimated results from the data panel regression model, note that the factors that significantly influence the value of Indonesian shrimp exports are the nominal GDP of the destination country, the rupiah exchange rate, economic distance, and the value of Indonesian shrimp exports in the previous year. The strategy in increasing the production capacity and competitiveness of domestic shrimp business actors is to maintain the availability and quality of shrimp farming resources, especially quality shrimp seeds.